Case report: High grade serous fallopian tube carcinoma with rare NRG1 gene fusion presenting as widespread peritoneal carcinomatosis - Crymes, Anthony; Evans, Mark G.; Adeyelu, Tolulope; Reid, Jack; Ibe, Ifegwu O.; Oberley, Matthew J.; Tseng, Jill H. (Frontiers in Oncology, 2024)
The discovery of gene fusions involving Neuregulin-1 (NRG1) within solid tumors has important therapeutic implications, as they are being actively explored as targets for emerging ERBB/ERBB2/ERBB3-directed anti-cancer agents. NRG1 fusions are very uncommon across all tumor types and are infrequently documented in the medical literature. We report a female patient presenting with widespread peritoneal carcinomatosis diagnosed as high grade serous fallopian tube carcinoma, which harbored a previously undescribed MYH10::NRG1 fusion. Moreover, we queried the whole transcriptome sequencing results of neoplasms analyzed by a commercial laboratory (Caris Life Sciences) to determine the overall incidence of NRG1 fusions in carcinomas of the ovary, fallopian tube, and peritoneum (0.18%). Twenty-five additional tumors were found to demonstrate NRG1 fusions, including 20 new genes partners that had not been previously identified in gynecologic carcinomas. Overall, NRG1 fusion events are rare in ovarian, fallopian tube, and primary peritoneal carcinomas, but they may carry diagnostic significance in the context of borderline/low grade serous tumors, which demonstrated exclusively CLU::NRG1 fusions, and could have important predictive implications for response to ERBB/ERBB2/ERBB3-directed therapies.